(untitled) (Jurnal Matematika, Statistika dan Komputasi, 2026)
This study discusses the dynamics of corrosion spread on reinforced concrete bridge reinforcement in coastal areas using the SIRS mathematical model approach and considering the Holling type III function. The model built, can be seen how corrosion appears, spreads, and persists based on the influence of interaction parameters between healthy reinforcement and reinforcement that has experienced damage. In addition, this model can be analyzed dynamically including the equilibrium point, local stability and basic reproduction number. The simulation results show that when the basic reproduction number , corrosion cannot persist and the system will return to a corrosion-free condition. However, when , corrosion is able to spread and persist so that some of the reinforcing steel remains in a corroded condition. Parameter analysis shows that increasing the ratio of the corrosion propagation rate to the recovery rate significantly increases the likelihood of corrosion development and long-term persistence. This ratio represents the intensity of interaction between the reinforcement in good condition and the corroded reinforcement